Prospective classroom teachers’ views on instructional technologies and web-based digital educational tools - Avcı, Görkem; Subaşıoğlu, Elvan (Institute of Advanced Engineering and Science, 2025)
This study examined prospective classroom teachers’ perceptions of instructional technologies and the web-based digital tools they actively use. Using a case study design with semi-structured interviews, data were collected from 15 prospective teachers who had completed an instructional technology course. The findings show that participants strongly emphasized the necessity of technology integration in education. The most commonly used tools included assessment, visual–infographic design, coding, drawing–shaping, augmented and virtual reality, animation, interactive presentations, and artificial intelligence. These tools were found to significantly support effective and efficient learning, enhance motivation, and promote sustainable learning. Accordingly, the study recommends the systematic use of web-based digital tools to support digital transformation in education.